Development and evaluation of brochures for fall prevention education created to empower nursing home residents and family members. (25th January 2018) - Schoberer, Daniela; Eglseer, Doris; Halfens, Ruud J.G.; Lohrmann, Christa
Abstract : Aims and objectives: In this study, we describe the development of evidence‐ and theory‐based fall prevention educational material and its evaluation from the users' perspectives. Background: To reduce risk factors for falling in nursing homes, nursing staff must enact multifactorial fall prevention intervention programmes. A core component of these programmes is to educate residents and their family members, both verbally and in a written form. However, users can only benefit from educational material if it is based on current scientific evidence, easy to understand and process and customised. Design: We followed a structured procedure during the development process, while considering various aspect of quality. To assess the understandability and usefulness of the resulting educational materials, we conducted a qualitative content analysis study. Methods: The educational materials development process incorporated several iterative steps including a systematic literature search and the application of frameworks for designing and writing the materials. To evaluate the material, we performed six focus group discussions separately with residents, family members and nursing staff from two nursing homes (total of 32 participants). Results: Residents' brochures included clear information on avoiding external risks as well as coping strategies after a fall event. Family members' brochures were more comprehensive, including both concrete tips and outlining the advantages and disadvantages of interventions. Residents and family members had no difficulties understanding the material and tried to apply the content to their individual situations. Nursing staff commented on some ambiguities and incongruities relating to current nursing care practice. Conclusions: By involving users in the development of evidence‐based educational materials, nursing staff can achieve a high acceptance rate for the materials and motivate users to address the topic. Implications for practice: The involvement of users is essential for developing educational material that meets users' needs. Educational material should be used as part of an overall strategy to educate residents and family members in nursing homes.